La mission d’Arménie des jésuites et la production des savoirs à la fin de l’Empire ottoman (1881-1914) - Philippe Bourmaud (European Journal of Turkish Studies)
Jesuit members of the mission of Armenia established in 1881 at the initiative of pope Leo XIII were prolific scientific authors. Their apostolic work across central Anatolia, from Marsovan/Merzifon to Adana, provided them with the occasion to become acquainted with and to chart the area from the perspectives of archaeology, epigraphy, church history, topography and ethnology. This article questions to what extent the Ottoman Empire was a relevant territorial framework for their research. Given the proclivities of the Jesuit missionaries towards the history of the early and byzantine Church, it might seem that their work skips such a reference. Such a conclusion would discount the primary goal of the mission: the Jesuits were sent on account of their involvement in science and in order to counteract the evolution of Anatolian Armenians towards nationalism that followed the Armenian cultural and linguistic revival of the nineteenth century. Through an examination of the biography and works of the members of the mission who published, of the construction of their scientific works in various disciplines, and through a comparison with the areas of interest of the Jesuit mission in Syria and its publication, this article concludes that, prior to the First World War, the Jesuits showed limited interest in covering the territory of the Ottoman Empire, but made the communal diversity of the Empire manifest, albeit with a propensity to impose on Ottoman society a heavily sectarian analytical grid.